Adaptive Spatial Lattice Manufacturing (ASLM): A novel approach to efficient lattice structure production - Justin Dirrenberger; Pierre Lapouge; Rachel Azulay; Peter Evers; Tom Vroemen (Materials & Design)
Adaptive Spatial Lattice Manufacturing (ASLM) represents a groundbreaking method for fabricating lattice structures by leveraging AI-driven robotic laser welding. Unlike traditional additive manufacturing techniques, ASLM corresponds to a direct assembly of solid rods, by welding, offering remarkable benefits in energy efficiency, dimensional accuracy, and scalability. This paper introduces the ASLM process, detailing its computational design principles, build mechanics, and material compatibility using AISI 316L stainless steel. Through mechanical characterization and finite element analysis, the structural performance of ASLM-produced lattices was evaluated, highlighting the predictability and reliability of their mechanical properties. Key findings demonstrate ASLM's capability to address critical limitations of conventional additive manufacturing methods, such L-PBF, LMD or EBM, while producing robust, scalable, and efficient designs. Challenges, including localized heat-affected zones and internal stress management, are also discussed, along with future prospects for multi-material integration and industrial applications in aerospace, construction, and beyond. ASLM establishes a transformative path for lattice manufacturing and advances the integration of architectured materials in diverse engineering domains.